Presence of the posterior pituitary bright spot sign on MRI in the general population: a comparison between 1.5 and 3T MRI and between 2D-T1 spin-echo- and 3D-T1 gradient-echo sequences - Klyn, Verena; Dekeyzer, Sven; Van Eetvelde, Ruth; Roels, Pieter; Vergauwen, Ortwin; Devolder, Pieter; Wiesmann, Martin; Achten, Eric; Nikoubashman, Omid (Pituitary, 2018)
Purpose To describe the prevalence of the posterior pituitary bright spot (PPBS) in the general population on 1.5 and 3T MRI examinations and on 2D-T1 spin-echo (SE) and 3D-T1 gradient-echo (GE) sequences. Materials and methods 1017 subjects who received an MRI of the brain for aspecific neurological complaints were included. MRI was performed on 1.5T in 64.5% and on 3T in 35.5% of subjects. Presence of the PPBS was evaluated on sagittal 2D T1-SE echo images with slice thickness 3 mm in 67.5% and on sagittal 3D T1-GE with slice thickness 0.9 mm in 32.5% of subjects. Results The PPBS was detectable in 95.9% of subjects. After correction for sex and age, no statistically significant difference could be seen concerning PPBS detection between 1.5 and 3T MRI examinations (p = 0.533), nor between 2D T1-SE and 3D T1-GE sequences (p = 0.217). There was a statistically significant association between increasing age and the absence of the PPBS (p < 0.001). The PPBS could not be identified in 6.2% of male subjects, compared to 2.2% of female subjects (p = 0.01). Discussion Absence of the PPBS can be seen in 4.1% of patients undergoing MRI of the brain for non-endocrinological reasons. Neither field-strength nor the use of a thick-sliced 2D T1-SE versus a thin-sliced 3D T1-GE sequence influenced the detectability of the PPBS. There is a statistically significant association between increasing age and male sex and the absence of the PPBS.